SOURCE INVERSION FOR ESTIMATING THE CONTINUOUS SLIP DISTRIBUTION ON A FAULT-INTRODUCTION OF GREEN'S FUNCTIONS CONVOLVED WITH A CORRECTION FUNCTION TO GIVE MOVING DISLOCATION EFFECTS IN SUBFAULTS - Sekiguchi H.; Irikura K.; Iwata T. (My University, 2002)
In order to obtain knowledge concerning the physics of earthquake rupturing more precisely and to obtain reliable source process for near-source ground motion simulation, we introduced a convolution method that incorporates the effect of a moving dislocation over a rectangular area to a synthetic point source into computing the element source waves for the waveform inversion. Therefore, the rupture directivity effect over the entire fault area is considered fully in the waveform inversion. The rupture process inverted using this technique has a continuous slip distribution inside the subfaults. The moment release history obtained for each subfault directly reflects a slip time function on the subfault because the rupture propagation effect inside each subfault is separated. The validity of this technique is based on the following approximation: the Green's functions from two point sources are approximately the same after a phase correction when the distances between two point sources is much smaller than the distance between the sources and an observation station. The condition for valid usage of this technique has been found through numerical tests. We applied this technique in the waveform inversion of strong motion records for the source process of the 1995 Hyogo-ken Nanbu earthquake. The global characteristics of moment release distributions are similar between two inversion results; one inverted with point-source element waveforms and the other with element source waves considering the finite moving dislocation effects inside each subfault. However, the details are different, e.g. the locations of local maxima of the total moment release are different between these inversion results. A positive correlation between final slip and peak slip velocity is observed.
Keywords: EARTHQUAKES; FAULTING; FAULT SLIP; RUPTURE PROPAGATION